2019
DOI: 10.1002/jcp.28917
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of microRNA‐149 activates SDF‐1/CXCR4 to promote osteogenic differentiation of mesenchymal stem cells

Abstract: MicroRNAs (miRs) involve in osteogenic differentiation and osteogenic potential of mesenchymal stem cells (MSCs). Accordingly, the present study aimed to further uncover role miR-149 plays in osteogenic differentiation of MSCs with the involvement of the stromal cell-derived factor-1 (SDF-1)/CXC chemokine receptor-4 (CXCR4) pathway.Initially, the osteogenic differentiation model was induced. Next, the positive expression of STRO-1 in periosteum, alkaline phosphatase (ALP) activity, osteocalcin (OCN) protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Among these components, SDF-1 and its receptor CXCR4 are crucial for bone marrow retention, mobilization, and are involved in homing and recruitment of stem cells to sites of injured tissues [17]. SDF-1 has been reported to be expressed in a wide range of issues, including those of the heart, skeleton, live, pancreas, endothelium, skin, and spinal cord [20,[32][33][34][35][36]. Recent studies suggest that the interaction of SDF-1 and CXCR4 could partially mediate the tra cking of MSCs to the impaired nucleus in the brain [20,37].…”
Section: Discussionmentioning
confidence: 99%
“…Among these components, SDF-1 and its receptor CXCR4 are crucial for bone marrow retention, mobilization, and are involved in homing and recruitment of stem cells to sites of injured tissues [17]. SDF-1 has been reported to be expressed in a wide range of issues, including those of the heart, skeleton, live, pancreas, endothelium, skin, and spinal cord [20,[32][33][34][35][36]. Recent studies suggest that the interaction of SDF-1 and CXCR4 could partially mediate the tra cking of MSCs to the impaired nucleus in the brain [20,37].…”
Section: Discussionmentioning
confidence: 99%
“…Another article confirmed the effect of miR-342-3p in osteogenic differentiation and explored the regulation mechanism between miR-342-3p and DNA methylation of its hosting gene EVL [37]. They found hypomethylation in the promoter of EVL promoted the miR-342-3p expression in osteogenic differentiation, Li et al [35] miRNA miR-29b MiR-29b targeted DNMT1 and led to the methylation modification in the Notch1 promoter, which affected the Notch signaling pathway and regulated the osteogenic differentiation in BMSCs.…”
Section: Osteogenic Differentiationmentioning
confidence: 91%
“…It revealed that miR-149 regulated MSCs osteogenic differentiation through epigenetic modifications ( Fig. 1) [35].…”
Section: Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…143 Further studies suggested that miR-149 mediated osteogenesis was steered by methyltransferases. 144 Contrasting findings regarding the role of Dnmts were reported during adipogenesis. While inhibition of Dnmt in multipotent C3H10T1/2 cells and 3T3-L1 preadipocytes favored adipogenesis, 145,146 upregulation of canonical Wnt signaling was demonstrated upon Dnmt inhibition in 3T3-L1 and ST2 mesenchymal precursor cells hindering adipogenesis.…”
Section: Fate Determinationmentioning
confidence: 92%